Abundances in field and globular cluster stars of the Galactic bulge: spectroscopy from the near-ultraviolet to the near-infrared - Ernandes, Heitor (2022)
The aim of this work is a better understanding of the formation and evolution of the Galactic bulge, and the nucleosynthesis that took place in the first stars that enriched the early bulge. The Galactic bulge is under intense discussion as concerns its origin and stellar populations. It contains very old metal-poor stars spacial distributed in a spheroidal shape that should have been formed at early times in an early process of bulge formation. The bulge has also a bar that formed from a thick disk probably. This component contains mostly metal-rich stars. The main aim of this work is to expand the studies of chemical abundances in different stellar populations in the Galactic bulge associated with the study of the nucleosynthesis processes. Chemical tagging of different groups of elements such as -, iron-peak, and heavy elements are considered presently as the key discriminator of stellar populations and nucleosynthesis processes. This work also relates to the prospects of the forthcoming instruments VLT-MOONS, VLT-CUBES, and ELT-MOSAIC in the studies of these stellar populations.